Positive electrode active material for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery

By solid -soluble SR in the lithium transition metal composite oxide and adjusting its distribution in the second particles, the problem of the lithium transition metal composite oxides with high NI content in non -hydraulics has been solved, which improves the battery Capacity and cycle characteristics.

CN119384733APending Publication Date: 2025-01-28PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380046170.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-29
Filing Date
2023-06-15
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Lithium transition metal composite oxides with Ni content of more than 80% are prone to side reactions in non-aqueous electrolytes, resulting in a decrease in charge and discharge cycle characteristics, and the prior art has failed to effectively improve this problem.

Method used

Utilize a positive active substance with a specified ratio of SR with a specified ratio of SR in the lithium transition metal composite oxides, and adjust the distribution of SR through the flight timing quadruple ion mass spectrometry method, so that the genius coefficient of the secondary particle surface is below 0.85, the internal internal The Gini coefficient is below 0.7, and the standardization intensity ratio is above 1 and below 5.

Benefits of technology

Through the proper SR scattered state, the side reaction of the lithium transition metal composite oxide and non -hydrolytic quality is improved, and the initial discharge capacity of the non -hydrolytic secondary battery and the loading loop characteristics are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119384733A_ABST
    Figure CN119384733A_ABST
Patent Text Reader

Abstract

Provided is a positive electrode active material for a non-aqueous electrolyte secondary battery, the positive electrode active material having improved charge / discharge cycle characteristics and high capacity. The positive electrode active material contained in the non-aqueous electrolyte secondary battery contains a lithium transition metal composite oxide, the lithium transition metal composite oxide contains Ni and Sr and contains secondary particles formed by aggregating primary particles, and in the element concentration distribution in the cross section of the lithium transition metal composite oxide using time-of-flight secondary ion mass spectrometry, the element concentration distribution in the cross section of the lithium transition metal composite oxide is greater than the element concentration distribution in the cross section of the lithium transition metal composite oxide, and the element concentration distribution is greater than the element concentration distribution in the cross section of the lithium transition metal composite oxide. The Gini coefficient of the surface of the secondary particle of Sr is 0.85 or less, the Gini coefficient of the interior of the secondary particle of Sr is 0.7 or less, and the ratio of the normalized intensity of Sr, ISrOUT, on the surface of the secondary particle to the normalized intensity of Sr, ISrIN, ISrOUT / ISrIN, on the interior of the secondary particle is from 1 to 5 (inclusive).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a positive electrode active material for a nonaqueous electrolyte secondary battery and a nonaqueous electrolyte secondary battery. Background Art

[0002] LiNiO 2 ) has a high energy density, and by replacing part of Ni with Co, Al, Mn, etc., battery characteristics such as reliability can be improved.

[0003] Patent Document 1 discloses a technique for improving the charge-discharge cycle characteristics and safety of a secondary battery by using a positive electrode active material in which Sr is solid-dissolved at a predetermined ratio in an NCM-based lithium transition metal composite oxide containing Ni, Co, and Mn.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent No. 6226430 Summary of the invention

[0007] However, the initial discharge capacity of lithium transition metal composite oxides with a Ni content of more than 80% is large, but it is easy to cause side reactions with non-aqueous electrolytes, so the charge and discharge cycle characteristics are sometimes reduced. The technology described in Patent Document 1 does not study the improvement of battery characteristics using lithium transition metal composite oxides with a high Ni content, and there is still room for improvement.

[0008] An object of the present disclosure is to provide a positive electrode active material that contributes to increasing the capacity and improving the charge-discharge cycle characteristics of a nonaqueous electrolyte secondary battery.

[0009] A positive electrode active material for a non-aqueous electrolyte secondary battery as one embodiment of the present invention is characterized in that it includes a lithium transition metal composite oxide, the lithium transition metal composite oxide contains Ni and Sr and includes secondary particles formed by aggregation of primary particles, in which, in the element concentration distribution of the cross section of the lithium transition metal composite oxide using time-of-flight secondary ion mass spectrometry, the Gini coefficient of the secondary particle surface of Sr is less than 0.85, the Gini coefficient of the secondary particle interior of Sr is less than 0.7, and the normalized intensity I of Sr on the surface of the secondary particle is less than 0. Sr_OUT Normalized intensity I relative to Sr inside secondary particles Sr_IN Ratio I Sr_OUT / I Sr_IN It is 1 or more and 5 or less.

[0010] A nonaqueous electrolyte secondary battery as one embodiment of the present disclosure is characterized by comprising a positive electrode including the positive electrode active material for a nonaqueous electrolyte secondary battery, a negative electrode, and a nonaqueous electrolyte.

[0011] According to the positive electrode active material for a nonaqueous electrolyte secondary battery as one embodiment of the present disclosure, the initial discharge capacity and charge-discharge cycle characteristics of the nonaqueous electrolyte secondary battery can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 It is a longitudinal cross-sectional view of a nonaqueous electrolyte secondary battery as an example of an embodiment. DETAILED DESCRIPTION

[0013] In the layered structure of the lithium transition metal composite oxide, there are transition metal layers, Li layers, and oxygen layers. The Li ions present in the Li layer reversibly enter and exit, thereby the charge and discharge reaction of the battery is carried out. Generally, lithium transition metal composite oxides with Ni as the main component are known as high-capacity positive electrode active materials. However, lithium transition metal composite oxides with a Ni content of more than 80% are prone to side reactions with non-aqueous electrolytes. Therefore, the products produced by the side reactions adhere to the surface of the lithium transition metal composite oxide, and the charge and discharge cycle characteristics are sometimes reduced.

[0014] Patent Document 1 discloses a technique for improving the charge-discharge cycle characteristics and safety of a secondary battery by using a positive electrode active material in which Sr is solid-dissolved at a predetermined ratio in a NCM-based lithium transition metal composite oxide containing Ni, Co, and Mn. However, Patent Document 1 does not study the improvement of battery characteristics using a lithium transition metal composite oxide with a high Ni content, and there is still room for improvement.

[0015] The inventors of the present invention have conducted in-depth research to solve the above-mentioned problems, and found that by using a lithium transition metal composite oxide in which Sr is present on the surface and inside of secondary particles at a predetermined ratio, it is possible to achieve both battery capacity and charge-discharge cycle characteristics. It is inferred that S forms an appropriate dispersion state in the lithium transition metal composite oxide, thereby suppressing side reactions with non-aqueous electrolytes during charge and discharge.

[0016] Hereinafter, an example of an embodiment of the non-aqueous electrolyte secondary battery disclosed in the present invention is described in detail. Hereinafter, a cylindrical battery in which a wound electrode body is accommodated in a cylindrical outer shell is exemplified, but the electrode body is not limited to the wound type, and may also be a stacked type in which a plurality of positive electrodes and a plurality of negative electrodes are alternately stacked one by one through a separator. In addition, the outer shell is not limited to a cylindrical shape, and may be, for example, a square shape, a coin shape, etc., or may be a battery shell composed of a laminate sheet including a metal layer and a resin layer.

[0017] Figure 1FIG. 1 is an axial cross-sectional view of a cylindrical secondary battery 10 as an example of an embodiment. Figure 1 As shown, the secondary battery 10 comprises: a wound electrode body 14, an electrolyte, and an outer case 16 for accommodating the electrode body 14 and the electrolyte. The electrode body 14 includes a positive electrode 11, a negative electrode 12, and a separator 13, and has a wound structure in which the positive electrode 11 and the negative electrode 12 are spirally wound with the separator 13 interposed therebetween. The outer case 16 is a metal container in a bottomed cylindrical shape with one side open in the axial direction, and the opening of the outer case 16 is blocked by a sealing body 17. In the following, for the sake of convenience of description, the sealing body 17 side of the battery is regarded as the upper side, and the bottom side of the outer case 16 is regarded as the lower side.

[0018] The positive electrode 11, the negative electrode 12 and the separator 13 constituting the electrode body 14 are all rectangular strips, and are alternately stacked along the radial direction of the electrode body 14 by spirally winding along the length direction. The separator 13 separates the positive electrode 11 and the negative electrode 12 from each other. The negative electrode 12 is formed to be one size larger than the positive electrode 11 to prevent lithium precipitation. That is, the negative electrode 12 is formed to be longer than the positive electrode 11 in the length direction and the width direction. Two separators 13 are formed to be at least one size larger than the positive electrode 11, for example, arranged in a manner of sandwiching the positive electrode 11. The electrode body 14 includes a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like. In the electrode body 14, the length direction of the positive electrode 11 and the negative electrode 12 is the winding direction, and the width direction of the positive electrode 11 and the negative electrode 12 is the axial direction. That is, the end faces of the positive electrode 11 and the negative electrode 12 in the width direction form the end faces of the electrode body 14 in the axial direction.

[0019] Insulating plates 18 and 19 are disposed above and below the electrode body 14 , respectively. Figure 1 In the example shown, the positive electrode lead 20 extends to the sealing body 17 side through the through hole of the insulating plate 18, and the negative electrode lead 21 extends to the bottom side of the outer shell 16 through the outer side of the insulating plate 19. The positive electrode lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing body 17 by welding or the like, and the top plate of the sealing body 17, that is, the cover 27 electrically connected to the internal terminal plate 23 serves as the positive terminal. The negative electrode lead 21 is connected to the bottom inner surface of the outer shell 16 by welding or the like, and the outer shell 16 serves as the negative terminal.

[0020] A gasket 28 is provided between the outer shell 16 and the sealing body 17 to ensure the airtightness inside the battery. A groove portion 22 is formed on the outer shell 16, with a portion of the side portion bulging inwardly for supporting the sealing body 17. The groove portion 22 is preferably formed in a ring shape along the circumferential direction of the outer shell 16, and the sealing body 17 is supported by its upper surface. The sealing body 17 is fixed to the upper part of the outer shell 16 by the groove portion 22 and the open end of the outer shell 16 that is tightly fitted to the sealing body 17.

[0021] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26 and a cover 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating member 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective central portions, and an insulating member 25 is sandwiched between their respective peripheral portions. When the internal pressure of the battery rises due to abnormal heat release, the lower valve body 24 is deformed and broken in a manner that pushes the upper valve body 26 toward the cover 27 side, thereby blocking the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure rises further, the upper valve body 26 breaks, and the gas is discharged from the opening of the cover 27.

[0022] Hereinafter, the positive electrode 11 , the negative electrode 12 , the separator 13 , and the nonaqueous electrolyte constituting the secondary battery 10 , particularly the positive electrode 11 , will be described in detail.

[0023] [positive electrode]

[0024] The positive electrode 11 includes, for example, a positive electrode current collector and a positive electrode mixture layer formed on the surface of the positive electrode current collector. The positive electrode mixture layer is preferably formed on both sides of the positive electrode current collector. The positive electrode current collector may be a foil of a metal such as aluminum or an aluminum alloy that is stable within the potential range of the positive electrode 11, or a thin film having the metal disposed on the surface. The thickness of the positive electrode current collector is, for example, 10 μm to 30 μm.

[0025] The positive electrode mixture layer includes, for example, a positive electrode active material, a conductive agent, and a binder. The thickness of the positive electrode mixture layer is, for example, 10 μm to 150 μm on one side of the positive electrode collector. The positive electrode 11 can be manufactured, for example, as follows: a positive electrode mixture slurry including a positive electrode active material, a conductive agent, etc. is applied to the surface of the positive electrode collector, and after the coating is dried, it is rolled to form a positive electrode mixture layer on both sides of the positive electrode collector, thereby being manufactured.

[0026] Examples of the conductive agent contained in the positive electrode mixture layer include carbon black (CB), acetylene black (AB), Ketjen black, carbon nanotubes (CNT), graphene, graphite and other carbonaceous particles, etc. These may be used alone or in combination of two or more.

[0027] As the binder contained in the positive electrode mixture layer, for example, fluorine resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), polyimide resins, acrylic resins, polyolefin resins, polyacrylonitrile (PAN), etc. can be cited. These can be used alone or in combination of two or more.

[0028] The positive electrode active material contained in the positive electrode mixture layer includes a lithium transition metal composite oxide. The lithium transition metal composite oxide contains Ni and Sr.

[0029] The content of Ni in the lithium transition metal composite oxide is 80 mol% or more relative to the total molar number of metal elements other than Li. Thus, the battery capacity can be improved. The content of Ni is preferably 85 mol% or more, more preferably 90 mol% or more. In addition, from the viewpoint of structural stabilization, the content of Ni is preferably 95 mol% or less.

[0030] The content of Sr in the lithium transition metal composite oxide is preferably 0.01 mol% to 1 mol%, more preferably 0.02 mol% to 0.5 mol%, and further preferably 0.05 mol% to 0.2 mol%, based on the total molar number of metal elements excluding Li.

[0031] The lithium transition metal composite oxide may further include one or more elements selected from the group consisting of Co, Al and Mn. The contents of Co, Al and Mn in the lithium transition metal composite oxide are, for example, 0 mol% to 10 mol% relative to the total molar number of metal elements other than Li. In addition, the total contents of Co, Al and Mn are, for example, 0 mol% to 18 mol%.

[0032] The lithium transition metal composite oxide may further include one or more elements selected from the group consisting of Nb, Ti, Zr, W and Si. The contents of Nb, Ti, Zr, W and Si in the lithium transition metal composite oxide are, for example, 0 mol% to 1 mol% relative to the total molar number of metal elements other than Li. In addition, the total contents of Nb, Ti, Zr, W and Si are, for example, 0 mol% to 2 mol%.

[0033] Lithium transition metal composite oxides are, for example, of the general formula Li a Ni x M1 y M2 z Sr s O 2-b (wherein, 0.8≤a≤1.2, 0.80≤x≤0.95, 0≤y≤0.18, 0≤z≤0.02, 0.0001≤s≤0.01, 0≤b≤0.05, x+y+z+s=1, M1 is one or more elements selected from the group consisting of Co, Al and Mn, and M2 is one or more elements selected from the group consisting of Nb, Ti, Zr, W and Si). The ratio of the metal elements contained in the lithium transition metal composite oxide can be measured, for example, using an inductively coupled plasma atomic emission spectrometer (ICP-AES).

[0034] The lithium transition metal composite oxide contains secondary particles formed by the aggregation of primary particles. The particle size of the primary particles is, for example, 0.02 μm to 2 μm. The particle size of the primary particles is measured as the diameter of the circumscribed circle in the particle image observed by a scanning electron microscope (SEM). The average particle size of the secondary particles is, for example, 2 μm to 30 μm. Here, the average particle size refers to the volume-based median particle size (D50). D50 refers to the particle size at which the accumulation of frequencies in the volume-based particle size distribution becomes 50% from the smaller particle size, and is also called the median diameter. The particle size distribution of the secondary particles can be measured using a laser diffraction particle size distribution measuring device (e.g., MT3000II manufactured by MicrotracBEL Corp.) using water as the dispersion medium.

[0035] Sr exists on the surface of secondary particles and inside the secondary particles. Sr exists inside the secondary particles, for example, on the surface of primary particles and is not dissolved inside the primary particles. As a result, the effect of suppressing the side reaction between the non-aqueous electrolyte and the lithium transition metal composite oxide becomes obvious. Sr can exist on the surface of secondary particles and inside the secondary particles as a compound containing Sr. Examples of compounds containing Sr include SrO, SrCO 3 The presence of Sr on the secondary particle surface and inside the secondary particle can be confirmed by, for example, energy dispersive X-ray spectroscopy (TEM-EDX) in addition to the time-of-flight secondary ion mass spectrometry described later.

[0036] In the element concentration distribution of the cross section of the lithium transition metal composite oxide using time-of-flight secondary ion mass spectrometry (TOF-SIMS), the Gini coefficient of the Sr secondary particle surface was less than 0.85, the Gini coefficient of the Sr secondary particle interior was less than 0.7, and the normalized intensity I of Sr on the secondary particle surface was less than 0.85. Sr_OUT Normalized intensity I relative to Sr inside secondary particles Sr_IN Ratio I Sr_OUT / I Sr_IN Satisfy 2≤I Sr_OUT / I Sr_IN ≤7(below, I Sr_OUT / I Sr_IN (referred to as the normalized intensity ratio of Sr). This improves the initial discharge capacity and charge-discharge cycle characteristics of the secondary battery 10. It is assumed that the primary particle surfaces including the secondary particle surfaces are appropriately protected on the secondary particle surfaces and inside the secondary particles.

[0037] The Gini coefficient of the secondary particle surface of Sr is as follows: The normalized intensity I of Sr on the secondary particle surface Sr_OUT, when the accumulation rate is expressed in order of intensity, the area enclosed by the diagonal line and the Lorentz curve is doubled. The Gini coefficient inside the secondary particle of Sr is as follows: For the normalized intensity I of Sr inside the secondary particle Sr_IN , when the accumulation rate is expressed in order of intensity, the area enclosed by the diagonal line and the Lorentz curve is doubled. The Gini coefficient becomes 0 in the case of complete uniformity, and the value increases as the uniformity decreases. The Gini coefficient inside the secondary particles of Sr can also be smaller than the Gini coefficient on the surface of the secondary particles of Sr. That is, Sr can also be more uniformly dispersed inside the secondary particles than on the surface of the secondary particles.

[0038] The normalized intensity ratio of Sr was obtained by measurement under the following conditions using a time-of-flight secondary ion mass spectrometer (TOF-SIMS5 manufactured by IONTOF Corporation).

[0039] Primary ion: Bi 3 +

[0040] Ion voltage: 30kV

[0041] Ion current: 0.03pA @ 100us

[0042] Observation range: 50μm×50μm

[0043] Mass range: 60us (~310amu)

[0044] Detection: 4frame / scan, 150scan

[0045] The image showing the concentration distribution of Ni and Sr obtained in the above measurement was divided into 256×256 pixels, and the detection intensity of Ni and Sr was calculated for each pixel. Furthermore, the ratio of the detection intensity of Sr to the detection intensity of Ni was calculated as the normalized intensity I of Sr. Sr .

[0046] The range from the surface of the secondary particle to the inner side of 0.5 μm identified in the above image is regarded as the surface of the secondary particle, and the pixels contained in the surface of the secondary particle (hereinafter referred to as surface pixels) are determined. Sr The collection becomes I Sr_OUT In addition, the inner side of the secondary particle surface determined in the above is regarded as the inner side of the secondary particle, and the pixels contained in the inner side of the secondary particle (hereinafter referred to as inner pixels) are determined. The I corresponding to each inner pixel Sr The collection becomes I Sr_IN . The I obtained in this way Sr_OUT and I Sr_IN , calculate the standardized intensity ratio of Sr (ISr_OUT / I Sr_IN ). In addition, by I Sr_OUT and I Sr_IN The Gini coefficient of Sr on the secondary particle surface and the Gini coefficient of Sr inside the secondary particle are calculated. The sample for cross-sectional observation may be a sample in which a lithium transition metal composite oxide is embedded in a resin or the like, or may be a positive electrode mixture layer containing a lithium transition metal composite oxide.

[0047] The lithium transition metal composite oxide may have a layered structure. As the layered structure of the lithium transition metal composite oxide, for example, a layered structure belonging to the space group R-3m, a layered structure belonging to the space group C2 / m, etc. can be cited. From the viewpoint of high capacity and stability of the crystal structure, the lithium transition metal composite oxide preferably has a layered structure belonging to the space group R-3m. The layered structure of the lithium transition metal composite oxide may include a transition metal layer, a Li layer, and an oxygen layer.

[0048] In the layered structure of the lithium transition metal composite oxide, the ratio of the metal element other than Li present in the Li layer is 8 mol% or less relative to the total molar number of the metal elements other than Li in the lithium transition metal composite oxide. When the ratio of the metal element other than Li in the Li layer exceeds 8 mol%, the diffusivity of the Li ions in the Li layer decreases, and the battery capacity sometimes decreases. The metal element other than Li present in the Li layer is mainly Ni, but other metal elements may also be included. The ratio of the metal element other than Li in the Li layer is, for example, 0.1 mol% or more.

[0049] The ratio of metal elements other than Li in the layered Li layer is obtained from the Rietveld analysis results of the X-ray diffraction spectrum of the lithium transition metal composite oxide by X-ray diffraction measurement. For example, PDXL2 (Rigaku Corporation), which is a Rietveld analysis software, can be used for the Rietveld analysis of the X-ray diffraction spectrum.

[0050] The X-ray diffraction spectrum was obtained by powder X-ray diffraction under the following conditions using a powder X-ray diffractometer (manufactured by Rigaku Corporation, trade name "RINT-TTR", radiation source: Cu-Kα).

[0051] Measuring range: 15-120°

[0052] Scanning speed: 4° / min

[0053] Resolution range: 30-120°

[0054] Background: B-Splines

[0055] Curve function: segmented pseudo-Voigt function

[0056] Constraint: Li(3a)+Ni(3a)=1

[0057] Ni(3a)+Ni(3b)=α (α is the Ni content ratio of each)

[0058] ICSD No.:98-009-4814

[0059] The positive electrode mixture layer may contain other positive electrode active materials in addition to the positive electrode active material of the present embodiment. As other positive electrode active materials, for example, lithium transition metal composite oxides containing Ni and Sr, with a Gini coefficient of more than 0.85 on the surface of secondary particles of Sr; lithium transition metal composite oxides with a Gini coefficient of more than 0.7 inside the secondary particles of Sr; lithium transition metal composite oxides with a normalized strength of less than 2 or more than 7 can be cited.

[0060] Next, an example of a method for producing a positive electrode active material according to the present embodiment is described. The method for producing a positive electrode active material includes, for example, the following steps: a step of mixing a metal oxide containing at least Ni with a Li raw material and a Sr raw material to obtain a mixture; and a step of calcining the mixture to obtain a positive electrode active material.

[0061] The metal oxide containing at least Ni can be prepared as follows: while stirring a solution containing a metal salt of Ni, Co, Al, Mn, etc., while dropping an alkaline solution such as sodium hydroxide, adjusting the pH to alkaline (e.g., 8.5 to 12.5), thereby precipitating a composite hydroxide (coprecipitation), and heat-treating the metal hydroxide, thereby preparing the metal oxide. The calcination temperature is not particularly limited, for example, in the range of 300° C. to 600° C.

[0062] Next, a metal oxide containing at least Ni is mixed with a Li raw material and a Sr raw material to obtain a mixture. Examples of the Li raw material include Li 2 CO 3 、LiOH、Li 2 O 2 , Li 2 O、LiNO 3 、LiNO 2 , Li 2 SO 4 、LiOH·H 2 O, LiH, LiF, etc. As the Sr raw material, Sr(OH) 2 、SrHPO 4 、Sr(H 2 PO 4 ) 2 , Sr3 (PO 4 ) 2 、SrO、SrCO 3 、SrSO 4 、Sr(NO 3 ) 2 、SrCl 2 、SrAlO 4 In addition, when mixing, Me raw materials can be mixed. Examples of Me raw materials include Nb 2 O 5 、TiO 2 、ZrO 2 , WO 3 、SiO 2 wait.

[0063] By calcining the above mixture, a lithium transition metal composite oxide as a positive electrode active material is obtained. The mixture is calcined, for example, in an oxygen atmosphere. The calcination conditions are as follows: the first heating rate of 300°C or more and 680°C or less is in the range of more than 1.0°C / minute and less than 4.5°C / minute, and the maximum temperature is in the range of more than 700°C and less than 850°C. The second heating rate from more than 680°C to the maximum temperature can be set to 0.1°C / minute to 3.5°C / minute, for example. In addition, the holding time to reach the maximum temperature can be more than 1 hour and less than 10 hours. In addition, the calcination process can be a multi-stage calcination, as long as the first heating rate and the second heating rate are within the above-defined range, and multiple can be set in each temperature zone. For example, by heating the first heating rate at a lower rate, the value of the Gini coefficient of Sr on the surface of the secondary particles and inside the secondary particles can be reduced.

[0064] The prepared lithium transition metal composite oxide can be washed and dried. The washing and drying can be carried out by known methods and conditions. It should be noted that Sr raw materials or Me raw materials can be added to the filter cake-like composition after washing.

[0065] [negative electrode]

[0066] The negative electrode 12 has, for example, a negative electrode current collector and a negative electrode mixture layer formed on the surface of the negative electrode current collector. The negative electrode mixture layer is preferably formed on both sides of the negative electrode current collector. As the negative electrode current collector, a foil of a metal such as copper or a copper alloy that is stable within the potential range of the negative electrode 12, a thin film having such a metal disposed on the surface layer, or the like can be used. The thickness of the negative electrode current collector is, for example, 5 μm to 30 μm. The negative electrode mixture layer contains, for example, a negative electrode active material and a binder. The thickness of the negative electrode mixture layer is, for example, 10 μm to 150 μm on one side of the negative electrode current collector. The negative electrode 12 can be produced, for example, by coating a negative electrode mixture slurry containing a negative electrode active material, a binder, etc. on the surface of the negative electrode current collector, drying the coating film, and then performing rolling to form the negative electrode mixture layer on both sides of the negative electrode current collector.

[0067] As the negative electrode active material contained in the negative electrode mixture layer, there is no particular limitation as long as it can reversibly store and release lithium ions, and carbon materials such as graphite are usually used. The graphite can be any of natural graphite such as flake graphite, massive graphite, and earthy graphite, massive artificial graphite, graphitized mesophase carbon microbeads, and other artificial graphite. In addition, as the negative electrode active material, metals alloyed with Li such as Si and Sn, metal compounds containing Si, Sn, etc., lithium titanium composite oxides, etc. can be used. In addition, those provided with a carbon coating film thereon can be used. For example, a Si-containing compound represented by SiO x (0.5 ≤ x ≤ 1.6), or a Si-containing compound in which fine particles of Si are dispersed in a lithium silicate phase represented by Li 2y SiO (2+y) (0 < y < 2) can be used in combination with graphite.

[0068] As the binder contained in the negative electrode mixture layer, for example, styrene-butadiene rubber (SBR), nitrile-butadiene rubber (NBR), carboxymethyl cellulose (CMC) or its salt, polyacrylic acid (PAA) or its salt (which can be PAA-Na, PAA-K, etc., and partially neutralized salts), polyvinyl alcohol (PVA), etc. can be cited. They can be used alone or in combination of two or more.

[0069] [Separator]

[0070] In the separator 13, a porous sheet having, for example, ion permeability and insulation is used. Specific examples of the porous sheet include microporous films, woven fabrics, non-woven fabrics, etc. As the material of the separator, polyolefins such as polyethylene and polypropylene, cellulose, etc. are suitable. The separator 13 can have a single-layer structure or a laminated structure. In addition, a resin layer having high heat resistance such as an aromatic polyamide resin, a filler layer containing a filler of an inorganic compound, etc. can be provided on the surface of the separator 13.

[0071] [Non-aqueous electrolyte]

[0072] The non-aqueous electrolyte, for example, comprises a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. For example, esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, and mixed solvents of more than two thereof can be used in the non-aqueous solvent. The non-aqueous solvent can contain a halogen substituted product formed by replacing at least a portion of the hydrogen atoms of these solvents with a halogen atom such as fluorine. As the halogen substituted product, fluorinated cyclic carbonates such as fluorinated ethylene carbonate (FEC), fluorinated chain carbonates, fluorinated chain carboxylates such as methyl fluoropropionate (FMP), etc. can be cited.

[0073] Examples of the above-mentioned esters include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate, chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate, cyclic carboxylates such as γ-butyrolactone (GBL) and γ-valerolactone (GVL), and chain carboxylates such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), and ethyl propionate.

[0074] Examples of the ethers include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, cyclic ethers such as crown ethers, 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether. , dihexyl ether, ethyl vinyl ether, butyl vinyl ether, methyl phenyl ether, ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether and other chain ethers, etc.

[0075] The electrolyte salt is preferably a lithium salt. Examples of lithium salts include LiBF 4 、LiClO 4 、LiPF 6 、LiAsF 6 、LiSbF 6 、LiAlCl 4 、LiSCN、LiCF 3 SO 3 、LiCF 3 CO 2 、Li(P(C 2 O 4 )F 4)、LiPF 6-x (C n F 2n+1 ) x (1 < x < 6, n is 1 or 2), LiB 10 Cl 10 、LiCl, LiBr, LiI, lithium chloroborate, lithium lower aliphatic carboxylate, Li 2 B 4 O 7 、Li(B(C 2 O 4 )F 2 ) and other borate salts, LiN(SO 2 CF 3 ) 2 、LiN(C 1 F 2l+1 SO 2 )(C m F 2m+1 SO 2 ) {l, m are integers of 0 or more} and other imide salts, etc. The lithium salt can be used alone or in combination of multiple kinds. Among these, from the viewpoints of ionic conductivity, electrochemical stability, etc., LiPF 6 is preferably used. The concentration of the lithium salt is, for example, 0.5 mol to 2 mol per 1 L of non-aqueous solvent. In addition, vinylene carbonate, propanesultone-based additives can be further added.

[0076] Examples

[0077] Hereinafter, the present disclosure will be further described based on examples and comparative examples, but the present disclosure is not limited to the following examples.

[0078] <Example 1-1>

[0079] [Production of positive electrode active material]

[0080] The composite hydroxide represented by [Ni 0.90 Co 0.05 Al 0.05 (OH) 2 obtained by the coprecipitation method was calcined at 500 °C for 8 hours to obtain a metal oxide (Ni 0.90 Co 0.05 Al 0.05 O 2 ). Then, Sr(OH) 2 was added to the above metal oxide so that the molar ratio of Sr to the total amount of Ni, Co, and Al became 0.05 mol%.Furthermore, lithium hydroxide monohydrate (LiOH·H 2 O) to obtain a mixture. The mixture was calcined from room temperature to 650°C at a first heating rate of 2°C / min under an oxygen gas flow with an oxygen concentration of 95% (a flow rate of 5 L / min per 1 kg of the mixture), and then calcined from 650°C to 720°C at a second heating rate of 1°C / min to obtain a lithium transition metal composite oxide. The lithium transition metal composite oxide was washed with water and dried to obtain the positive electrode active material of Example 1-1.

[0081] The positive electrode active material was measured using an ICP emission spectrophotometer (ICP-AES), and the elements shown in Table 1 described below were confirmed as elements other than Li and O. The element concentration distribution of the cross section of the positive electrode active material was measured using time-of-flight secondary ion mass spectrometry (TOF-SIMS), and the standardized intensity ratio (I Sr_OUT / I Sr_IN ) is 1.1, and the Gini coefficients inside and on the surface of the secondary particles of Sr are 0.67 and 0.84, respectively. The ratio of the metal elements other than Li present in the Li layer is 2.1 mol% relative to the total molar number of the metal elements other than Li in the lithium transition metal composite oxide.

[0082] [Production of positive electrode]

[0083] 95 parts by mass of the above-mentioned positive electrode active material are mixed with 3 parts by mass of acetylene black (AB) and 2 parts by mass of polyvinylidene fluoride (PVDF), and an appropriate amount of N-methyl-2-pyrrolidone (NMP) is further added to prepare a positive electrode mixture slurry. Next, the positive electrode mixture slurry is applied to both sides of a positive electrode collector formed of aluminum foil with a thickness of 15 μm, and after the coating is dried, the coating is rolled using a calendering roller, cut into a specified electrode size, and a positive electrode is prepared. It should be noted that a portion of the positive electrode is provided with an exposed portion exposed on the surface of the positive electrode collector.

[0084] [Production of negative electrode]

[0085] Natural graphite is used as the negative electrode active material. The negative electrode active material is mixed with sodium carboxymethyl cellulose (CMC-Na) and styrene-butadiene rubber (SBR) in an aqueous solution at a solid content mass ratio of 100:1:1 to prepare a negative electrode mixture slurry. Next, the negative electrode mixture slurry is applied to both sides of a negative electrode collector formed of copper foil, and after the coating film is dried, the coating film is rolled using a calendering roller and cut into a specified electrode size to produce a negative electrode. It should be noted that a portion of the negative electrode is provided with an exposed portion where the surface of the negative electrode collector is exposed.

[0086] [Preparation of non-aqueous electrolyte]

[0087] Ethylene carbonate (EC), ethyl methyl carbonate (MEC) and dimethyl carbonate (DMC) were mixed in a volume ratio of 3:3:4. Lithium hexafluorophosphate (LiPF 6 ) was dissolved in the mixed solvent at a concentration of 1.2 mol / L to prepare a non-aqueous electrolyte.

[0088] [Production of test battery cells]

[0089] A positive electrode lead is installed on the exposed part of the positive electrode, and a negative electrode lead is installed on the exposed part of the negative electrode. The positive electrode and the negative electrode are wound into a spiral shape with a polyolefin separator interposed therebetween, and then press-formed in the radial direction to produce a flat wound electrode body. The electrode body is housed in an outer shell composed of an aluminum laminate sheet, and after the above-mentioned non-aqueous electrolyte is injected, the opening of the outer shell is sealed to obtain a test battery cell.

[0090] [Evaluation of initial discharge capacity and capacity retention rate]

[0091] At an ambient temperature of 25°C, the test battery cell was charged at a constant current of 0.3C to 4.2V, then charged at a constant voltage of 4.2V to 0.02C, and then discharged at a constant current of 0.5C to 2.5V. The discharge capacity at this time was taken as the initial discharge capacity. This charge and discharge was regarded as one cycle, and 300 cycles were performed. The capacity retention rate of the test battery cell in the charge and discharge cycle was calculated according to the following formula.

[0092] Capacity retention rate = (discharge capacity at the 300th cycle / discharge capacity at the 1st cycle) × 100

[0093] <Examples 1-2, 1-3>

[0094] In the preparation of the positive electrode active material, the amount of Sr(OH) added was changed so that the molar ratio of Sr to the total amount of Ni, Co and Al became the value shown in Table 1. 2 A test battery cell was prepared and evaluated in the same manner as in Example 1-1 except that the amount was .

[0095] <Comparative Example 1-1>

[0096] In the preparation of the positive electrode active material, Sr(OH) was not added to the metal oxide. 2 SrCl was added to the filter cake composition after washing so that the molar ratio of Sr to the total amount of Ni, Co and Al became the value shown in Table 1. 2A test battery cell was prepared and evaluated in the same manner as in Example 1-1 except that the first temperature increase rate was changed to 5° C. / min and the second temperature increase rate was changed to 3° C. / min.

[0097] <Comparative Examples 1-2, 1-3>

[0098] In the preparation of the positive electrode active material, the amount of Sr(OH) added was changed so that the molar ratio of Sr to the total amount of Ni, Co and Al became the value shown in Table 1. 2 A test battery cell was prepared and evaluated in the same manner as in Example 1-1 except that the first temperature increase rate was changed to 5° C. / min and the second temperature increase rate was changed to 3° C. / min.

[0099] <Example 2-1>

[0100] In the preparation of the positive electrode active material, the composition of the metal oxide is changed to Ni 0.93 Al 0.04 Mn 0.03 Sr(OH) was added so that the molar ratio of Sr to the total amount of Ni, Al and Mn became 0.09 mol %. 2 , except for this, a test battery cell was prepared and evaluated in the same manner as in Example 1-1.

[0101] <Examples 2-2 to 2-4>

[0102] In the preparation of the positive electrode active material, ZrO was further added so that the molar ratio of Zr, Ti or Nb to the total amount of Ni, Al and Mn became the value shown in Table 2. 2 、TiO 2 or Nb 2 O 5 , except that a mixture was prepared, a test battery cell was prepared and evaluated in the same manner as in Example 2-1.

[0103] <Comparative Example 2-1>

[0104] In the preparation of the positive electrode active material, a test cell was prepared and evaluated in the same manner as in Example 2-1 except that the first temperature increase rate was changed to 5° C. / min and the second temperature increase rate was changed to 3° C. / min.

[0105] <Example 3-1>

[0106] In the preparation of the positive electrode active material, the composition of the metal oxide is changed to Ni 0.90 Co 0.04 Mn 0.06Sr(OH) was added so that the molar ratio of Sr to the total amount of Ni, Co and Mn became 0.09 mol %. 2 , except for this, a test battery cell was prepared and evaluated in the same manner as in Example 1-1.

[0107] <Examples 3-2 to 3-8>

[0108] In the preparation of the positive electrode active material, Nb was further added so that the molar ratio of Nb, Zr, W, Ti or Si relative to the total amount of Ni, Co and Mn became the value shown in Table 3. 2 O 5 、ZrO 2 , WO 3 、TiO 2 or SiO 2 , except that a mixture was prepared, a test battery cell was prepared and evaluated in the same manner as in Example 3-1.

[0109] <Comparative Example 3-1>

[0110] In the preparation of the positive electrode active material, a test cell was prepared and evaluated in the same manner as in Example 3-1 except that the first temperature increase rate was changed to 5° C. / min and the second temperature increase rate was changed to 3° C. / min.

[0111] <Example 4-1>

[0112] In the preparation of the positive electrode active material, the composition of the metal oxide is changed to Ni 0.90 Mn 0.10 Sr(OH) was added so that the molar ratio of Sr to the total amount of Ni and Mn was 0.10 mol %. 2 , except for this, a test battery cell was prepared and evaluated in the same manner as in Example 1-1.

[0113] <Comparative Example 4-1>

[0114] In the preparation of the positive electrode active material, a test cell was prepared and evaluated in the same manner as in Example 4-1 except that the first temperature increase rate was changed to 5° C. / min and the second temperature increase rate was changed to 3° C. / min.

[0115] The evaluation results of the test cells of the embodiments and comparative examples are shown in Tables 1 to 4. In addition, Tables 1 to 4 each show the composition of the metal oxide used in the preparation of the positive electrode active material and the ratio of the additives, the normalized intensity ratio and the Gini coefficient of Sr, and the ratio of the metal elements other than Li in the Li layer. In Table 1, the initial discharge capacity and capacity retention rate of the test cells other than Comparative Example 1-1 are expressed relative to the initial discharge capacity and capacity retention rate of the test cell of Comparative Example 1-1 as 100. In Table 2, the initial discharge capacity and capacity retention rate of the test cells other than Comparative Example 2-1 are expressed relative to the initial discharge capacity and capacity retention rate of the test cell of Comparative Example 2-1 as 100. In Table 3, the initial discharge capacity and capacity retention rate of the test cells other than Comparative Example 3-1 are expressed relative to the initial discharge capacity and capacity retention rate of the test cell of Comparative Example 3-1 as 100. In Table 4, the initial discharge capacity and capacity retention rate of the test cells other than Comparative Example 4-1 are expressed relative to each other, with the initial discharge capacity and capacity retention rate of the test cell of Comparative Example 4-1 being 100, respectively.

[0116] [Table 1]

[0117]

[0118] [Table 2]

[0119]

[0120] [Table 3]

[0121]

[0122] [Table 4]

[0123]

[0124] In Tables 1 to 4, the capacity retention rate of the test battery cell of the embodiment is higher than that of the test battery cell of the comparative example. In addition, the initial discharge capacity of the test battery cell of the embodiment is equal to or higher than the initial discharge capacity of the test battery cell of the comparative example. It can be seen that by having the Gini coefficient of the surface of the secondary particles containing Sr in the positive electrode active material be less than 0.85, the Gini coefficient inside the secondary particles of Sr be less than 0.7, and the normalized intensity I of Sr on the surface of the secondary particles be less than 1.0. Sr_OUT Normalized intensity I relative to Sr inside secondary particles Sr_IN Ratio I Sr_OUT / I Sr_IN The lithium transition metal composite oxide is 1 or more and 5 or less, so that both the battery capacity and the charge and discharge cycle characteristics can be achieved.

[0125] The present disclosure is further described according to the following embodiments.

[0126] Composition 1:

[0127] A positive electrode active material for a non-aqueous electrolyte secondary battery, comprising a lithium transition metal composite oxide,

[0128] The lithium transition metal composite oxide contains Ni and Sr and includes secondary particles formed by aggregation of primary particles.

[0129] In the element concentration distribution of the cross section of the lithium transition metal composite oxide using time-of-flight secondary ion mass spectrometry,

[0130] The Gini coefficient of the surface of the secondary particles of Sr is 0.85 or less, and the Gini coefficient of the inside of the secondary particles of Sr is 0.7 or less,

[0131] The normalized intensity I of Sr on the surface of the secondary particles is Sr_OUT Relative to the normalized intensity I of Sr inside the secondary particles Sr_IN Ratio I Sr_OUT / I Sr_IN It is 1 or more and 5 or less.

[0132] Composition 2:

[0133] The positive electrode active material for a non-aqueous electrolyte secondary battery according to configuration 1, wherein the content of Ni in the lithium transition metal composite oxide is 80 mol % or more relative to the total number of moles of metal elements other than Li in the lithium transition metal composite oxide.

[0134] Composition 3:

[0135] The positive electrode active material for a non-aqueous electrolyte secondary battery according to configuration 1 or 2, wherein

[0136] The lithium transition metal composite oxide has a layered structure.

[0137] The ratio of the metal element other than Li present in the Li layer of the layered structure is 8 mol% or less relative to the total number of moles of the metal element other than Li in the lithium transition metal composite oxide.

[0138] Composition 4:

[0139] The positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of Configurations 1 to 3, wherein the lithium-transition metal composite oxide further contains one or more elements selected from the group consisting of Co, Al, and Mn.

[0140] Composition 5:

[0141] The positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of Configurations 1 to 4, wherein the lithium-transition metal composite oxide further contains one or more elements selected from the group consisting of Nb, Ti, Zr, W, and Si.

[0142] Composition 6:

[0143] A nonaqueous electrolyte secondary battery comprises: a positive electrode including the positive electrode active material for a nonaqueous electrolyte secondary battery according to any one of configurations 1 to 5, a negative electrode, and a nonaqueous electrolyte.

[0144] Description of Reference Numerals

[0145] 10 secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 16 outer shell, 17 sealing body, 18, 19 insulating plate, 20 positive electrode lead, 21 negative electrode lead, 22 groove portion, 23 internal terminal plate, 24 lower valve body, 25 insulating member, 26 upper valve body, 27 cover, 28 gasket.

Claims

1. A positive electrode active material for a non-aqueous electrolyte secondary battery, comprising a lithium transition metal composite oxide, The lithium transition metal composite oxide contains Ni and Sr and includes secondary particles formed by aggregation of primary particles. In the element concentration distribution of the cross section of the lithium transition metal composite oxide using time-of-flight secondary ion mass spectrometry, The Gini coefficient of the surface of the secondary particles of Sr is 0.85 or less, and the Gini coefficient of the inside of the secondary particles of Sr is 0.7 or less, The normalized intensity of Sr on the secondary particle surface is Sr_OUT Relative to the normalized intensity I of Sr inside the secondary particle Sr_IN Ratio I Sr_OUT / I Sr_IN It is 1 or more and 5 or less.

2. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein The content of Ni in the lithium transition metal composite oxide is 80 mol % or more relative to the total number of moles of metal elements other than Li in the lithium transition metal composite oxide.

3. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein The lithium transition metal composite oxide has a layered structure. The ratio of the metal element other than Li present in the Li layer of the layered structure is 8 mol % or less relative to the total number of moles of the metal element other than Li in the lithium transition metal composite oxide.

4. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein The lithium transition metal composite oxide further contains one or more elements selected from the group consisting of Co, Al, and Mn.

5. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein The lithium transition metal composite oxide further includes one or more elements selected from the group consisting of Nb, Ti, Zr, W, and Si. 6 . A non-aqueous electrolyte secondary battery comprising: a positive electrode comprising the positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 , a negative electrode, and a non-aqueous electrolyte.

Citation Information

Patent Citations

  • All season type cooling, dehumidifying and heating device for use in painting

    JP1987026430A